2003
DOI: 10.1021/jf0343229
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Quinones on Colletotrichum Species

Abstract: The antifungal activity of 1,4-naphthoquinones, 1,2-naphthoquinones, 1,4-benzoquinones, and anthraquinones from our natural products collection was tested by direct bioautography to identify natural products with potential use in agricultural fungal pathogen control. Quinones demonstrated good to moderate antifungal activity against Colletotrichum spp. Colletotrichum fragariae was the most sensitive species to quinone-based chemistry, Colletotrichum gloeosporioides had intermediate sensitivity, while Colletotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 30 publications
2
58
0
1
Order By: Relevance
“…Finally, Guerrero-Rodriguez et al (2007) achieved a 93% growth inhibition of C. gloeosporioides with methanolchloroform extracts of Flourensia cernua. With regard to the use of essential oils of different plants, some reports showed inhibition percentages between 50% and 60% (Meepagala et al 2002;Meazza et al 2003). Somda et al (2007) reported a significant inhibition of C. gloeosporioides and Colletotrichum graminicola with lemongrass, eucalyptus, and neem essential oils at concentrations near 1,000 mg/L.…”
Section: Antifungal Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Guerrero-Rodriguez et al (2007) achieved a 93% growth inhibition of C. gloeosporioides with methanolchloroform extracts of Flourensia cernua. With regard to the use of essential oils of different plants, some reports showed inhibition percentages between 50% and 60% (Meepagala et al 2002;Meazza et al 2003). Somda et al (2007) reported a significant inhibition of C. gloeosporioides and Colletotrichum graminicola with lemongrass, eucalyptus, and neem essential oils at concentrations near 1,000 mg/L.…”
Section: Antifungal Assaymentioning
confidence: 99%
“…Nevertheless, C. gloeosporioides has developed resistance to some synthetic chemical fungicides such as benzimidazoles and quinones (Meazza et al 2003). On the other hand, the increasing demand for more "natural" food has led the research for alternative antimicrobial agents within the food industry (Davidson 1997;López-Malo et al 2000;Guynot et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, systematic studies of naphthoquinone derivatives have revealed compounds with anticancer (O'Brien, 1991;Lamson and Plaza, 2003;Taper et al, 2004), antifungal (Meazza et al, 2003, Tandon et al, 2004, antibacterial (Medina et al, 2004, Machado et al, 2003, antithrombotic (Jin et al, 2004) and antiparasitic (Kayser et al, 2003) activity, which may be valuable for use in conventional medicine.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, it was of interest that 1,2-naphthoquinone (ortho) was reported to be less active than its isomer, 1,4-naphthoquinone (para) against filamentous fungi, Colletrichum spp. 9 The vapor activity of quinones was examined using an agar vapor assay and a box vapor assay; the results are shown in Table 2 together with the activity by agar diffusion assay. The agar vapor assay detected this activity not only of a highly volatile compound but also of a poorly volatile compound, because the distance from the origin of the vapor to the organism was very small (4 mm).…”
mentioning
confidence: 99%